Maximum principles for hypersurfaces with vanishing curvature functions in an arbitrary Riemannian manifold - FONTENELE,FRANCISCO X. (2002)
In this paper we generalize and extend to any Riemannian manifold maximum principles for Euclidean hypersurfaces with vanishing curvature functions obtained by Hounie-Leite.